Cinephiles! as post-zine cinephilia in the age of digital networks - Mendizabal, Adrian D. (2017)
Access online through this link: https://www.plarideljournal.org/article/cinephiles-post-zine-cinephiliain-age-digital-networks
Keywords: Appreciation of motion pictures; Film criticism; Discussion